The Effects of Adolescent-Parent Attachment, Emotion Regulation, and Self-Esteem on Problematic Internet Use (PIU) among Adolescents - Adiningrum, Wastiti; Edy Wibowo, Mungin; Purwanto, Edy (Jurnal Bimbingan Konseling, 2022)
Technological developments, including the internet, are experiencing rapid progress. However, the internet can have a negative impact when its use is inappropriate, or called as problematic internet use (PIU). This study aimed to analyze the effects of parent-adolescent attachment, emotional regulation and self-esteem on problematic internet use (PIU). It involved 120 adolescents at public high schools throughout Tasikmalaya City using a purposive sampling technique. The questionnaires used in this study were the Adolescent Attachment Questionnaire (AAQ), Emotion Regulation Questionnaire (ERQ), Rosenberg Self-Esteem Scale (RSES), and Generalized Problematic Internet Use Scale 2 (GPIUS 2). In analyzing the data, descriptive and multiple linear regression tests were used. The results of this study proved that parent-adolescent attachment had a positive effect on problematic internet use (PIU), emotional regulation had a positive effect on problematic internet use (PIU), self-esteem had a positive effect on problematic internet use (PIU). Lastly, it was revealed that parent-adolescent attachment, emotional regulation and self-esteem simultaneously had positive effects on problematic internet use (PIU). Further, implications and limitations of this study are discussed in the discussion.